Identification of a novel helitron transposon in the genome of Antarctic fish - Cocca E; De Iorio S; CAPRIGLIONE, TERESA (Molecular Phylogenetics and Evolution, 2011)
A novel helitron from the genome of the icefish species Chionodraco hamatus, belonging to the Channichthyidae, the most derived Notothenioids family, was isolated, characterized and designated as HeliNoto (8.9 kb). Its ORF was compared to homologous sequences from different species in a comprehensive phylogenetic analysis. For the first time the putative functional domains of a helitron were subjected to a well accurate structural analysis including chromosomal localization. Finally, the distribution of HeliNoto among Notothenioids was investigated.